2016
DOI: 10.1016/j.jhin.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid as a decontamination method for sink drains in a nosocomial outbreak of metallo-β-lactamase-producing Pseudomonas aeruginosa

Abstract: Acetic acid is highly effective against Pae-MBL biofilms, and may be used as a simple method to decontaminate sink drains and to prevent nosocomial transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 15 publications
3
48
0
Order By: Relevance
“…Various plumbing components have been implicated in MDRGN outbreaks including sinks and washbasins in separate outbreaks of CRE, MDR P. aeruginosa and polyspecies German imipenemase-1 (GIM-1) [18][19][20][21], sink faucet aerators in a CRPA outbreak [22], and multiple plumbing components from the sink drains to wall pipes in a CRPA outbreak [23]. In a CR Sphingomonas koreensis outbreak, sink aerators, faucets, mixing valves, pipes and other plumbing fixtures were also found to be contaminated [24].…”
Section: Outbreak Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various plumbing components have been implicated in MDRGN outbreaks including sinks and washbasins in separate outbreaks of CRE, MDR P. aeruginosa and polyspecies German imipenemase-1 (GIM-1) [18][19][20][21], sink faucet aerators in a CRPA outbreak [22], and multiple plumbing components from the sink drains to wall pipes in a CRPA outbreak [23]. In a CR Sphingomonas koreensis outbreak, sink aerators, faucets, mixing valves, pipes and other plumbing fixtures were also found to be contaminated [24].…”
Section: Outbreak Reportsmentioning
confidence: 99%
“…Shower drains have also been implicated with CRPA outbreak [25]. In a study by Stjärne et al, investigation of a CRPA outbreak revealed contamination of sinks with isolates closely related to CRPA from patients [23]. Following sink replacement, CRPA reappeared on sink surveillance cultures after a mean duration of 13 weeks.…”
Section: Outbreak Reportsmentioning
confidence: 99%
“…U-bend biofilms are usually heterogenous communities consisting of a range of opportunistic bacterial pathogens, including Pseudomonas spp., Acinetobacter spp., Klebsiella spp. and Enterobacter spp., which can exhibit resistance to the major classes of antibiotics [2,4,6,10]. Furthermore, recent reports are increasingly highlighting the importance of wastewater pipework as a reservoir for the nosocomial transmission of carbapenemase-producing Enterobacteriaceae, an emerging global health threat [11].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of approaches to U-bend decontamination have been investigated with varying success, most of which involve disruption to service and have financial implications, including the replacement of fixtures and/or associated pipework [2,6,10]. Replacement is ineffective in the long term as new washbasins and pipework rapidly become recolonized with micro-organisms.…”
Section: Introductionmentioning
confidence: 99%
“…These communities will be exposed to liquids and waste that are discarded in a sink and may include antimicrobials, discarded beverages, soap, presumably pathogenic bacteria from health care workers' hands, and other items. In short, sink traps could serve as a breeding ground for opportunistic and highly antimicrobial-resistant bacteria that cannot be easily cleaned or removed (23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%